2010
DOI: 10.1128/jvi.00036-10
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evidence of Glycoprotein Assembly in Cellular Membrane Compartments prior to Alphavirus Budding

Abstract: Membrane glycoproteins of alphavirus play a critical role in the assembly and budding of progeny virions. However, knowledge regarding transport of viral glycoproteins to the plasma membrane is obscure. In this study, we investigated the role of cytopathic vacuole type II (CPV-II) through in situ electron tomography of alphavirus-infected cells. The results revealed that CPV-II contains viral glycoproteins arranged in helical tubular arrays resembling the basic organization of glycoprotein trimers on the envel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 38 publications
3
68
0
1
Order By: Relevance
“…These structures contain helical tubular arrays of viral glycoproteins within the vesicles, which are studded with nucleocapsids on their cytoplasmic face (91)(92)(93). Their proximity to the PM suggests that CPV-IIs may be an assembly intermediate (92), but it is not clear whether they are necessary for efficient infection or contribute to pathogenesis. CHIKV CPV-I and CPV-II structures also have been observed in mosquito cells (91).…”
Section: Disease Mechanisms and Host Immune Responsesmentioning
confidence: 99%
“…These structures contain helical tubular arrays of viral glycoproteins within the vesicles, which are studded with nucleocapsids on their cytoplasmic face (91)(92)(93). Their proximity to the PM suggests that CPV-IIs may be an assembly intermediate (92), but it is not clear whether they are necessary for efficient infection or contribute to pathogenesis. CHIKV CPV-I and CPV-II structures also have been observed in mosquito cells (91).…”
Section: Disease Mechanisms and Host Immune Responsesmentioning
confidence: 99%
“…Recent evidence has suggested that NCs and envelope proteins cotraffic from cytoplasmic domains to the plasma membrane on virus-induced membrane structures termed cytopathic vacuoles type II (CPV-II), and NC and the envelope proteins likely interact on these CPV-II structures (19,41). Furthermore, a morphologically distinct virus-induced membrane structure, termed cytopathic vacuole type I (CPV-I), likely contains the viral replicase and has been implicated as the site of initial NC assembly (11).…”
Section: Discussionmentioning
confidence: 99%
“…Soonsawad and colleagues showed that CPV-II vacuoles contain envelope proteins spikes, are decorated with NCs, and traffic from sites internal to the cell to the plasma membrane (41). Unpublished electron tomography data (T. J. Edwards and R. J. Kuhn) have demonstrated the movement of assembled NCs from CPV-I vacuoles to CPV-II vacuoles, and recent studies using microinjection of viral RNA into envelope protein-expressing cells demonstrated a preference for newly synthesized envelope proteins during envelopment of NCs (39).…”
Section: Fig 8 Em Analysis Of Cells Infected With Double Cde2/capsid mentioning
confidence: 99%
See 2 more Smart Citations